Primary cutaneous marginal zone lymphoma treated with doxycycline in a pediatric patient. Issue 4 (23rd April 2020) - Jothishankar, Balaji; Di Raimondo, Cosimo; Mueller, Lisa; Zain, Jasmine; Parekh, Vishwas; Abdulla, Farah
Abstract: We present the third reported case of a primary cutaneous marginal zone lymphoma (PCMZL) treated with doxycycline in a pediatric patient with negative serology for Borrelia burgdorferi . A 14‐year‐old boy presented with multiple asymptomatic erythematous papules and nodules on his extremities and trunk which biopsy confirmed to be PCMZL. He was started on doxycycline and experienced a near‐complete response. Given the favorable side effect profile of doxycycline and the indolent nature of PCMZL, we believe doxycycline is a possible therapy for PCMZL pediatric patients who have widely disseminated cutaneous disease.